GaInNAs/Ge (1.10/0.67 eV) double-junction solar cell grown by metalorganic chemical vapor deposition for high efficiency four-junction solar cell application. (26th October 2015) - Zhang, Xiaobin; Chen, Bingzhen; Pan, Xu; Wang, Lei; Ma, Difei; Zhang, Yang; Yang, Cuibai; Wang, Zhiyong
Abstract: GaInNAs materials with narrow bandgaps of 1.10 eV have been grown on a Ge substrate by metalorganic chemical vapor deposition to fabricate GaInNAs/Ge (1.10/0.67 eV) double-junction solar cells. We have studied the photovoltaic characteristics and the external quantum efficiencies of the double-junction cells with various annealing conditions and different GaInNAs base layer thicknesses. The best external quantum efficiency is obtained from the double-junction cell with a 1170 nm thick GaInNAs base layer annealed at 675 °C for 30 min. Under AM1.5G illumination, the best double-junction cell has a short circuit current density ( J SC ) as 23.63 mA cm −2, which is dominated by the J SC of the GaInNAs subcell.